Penularan Penyakit Mosaik Kacang Panjang oleh Aphis craccivora - Y. B. Sumardiyono; Supratoyo Supratoyo; Samsuri Samsuri (Universitas Gadjah Mada, 1997)
Transmission of cowpea mosaic disease (Vigna unguiculata (L.) Walp.) caused by Cowpea Aphid-borne Mosaic Virus (CAMV) through insect vector Aphis craccivora Koch was studied tn the laboratory and the field. Serial inoculation test in varied inoculation access period (1, 5, 10, and 15 minutes) was done to determine the retention time of virus. Field studies were undertaken to evaluate the effect of the number of initial inoculum and plant age on the disease progress. The results showed that viruliferous insect retained their inoculativity untill third series inoculation with 5, 10, and 15 minutes inoculation access period. lt indicated that the longest retention time was 45 minutes, and virus - insect relationship is non-persistent. The disease-spread changed with the number of initial inoculum and the age of the plant. The highest disease intensity of 97.92 per cent was observed in the plot with 2 diseased plants as inittal inoculum and the insects vectors were infested at 10 days plant of age. While the lowest was observed in the plot with one diseased plant as initial inoculum and infestation of insects vector at 30 days after planting.